MODERN ORGANIZATIONAL MANAGEMENT MODEL OF LOCAL GOVERNMENT ORGANIZATIONS IN PHETCHABURI PROVINCE - Songkram, Samnavathana Rtn; Decha, Puangngam (Journal of MCU Phetchaburi Review, 2025)
This research aimed to 1) study the current status, problems, and obstacles of local administrative management in Phetchaburi Province; 2) study the components of modern organizational management development; and 3) develop a modern organizational management model for local administrative organizations in Phetchaburi Province. This research utilized a mixed-methods approach, including qualitative (17 participants) and operational (15 participants). The findings revealed that the main challenges of local administration are budget constraints, personnel, bureaucracy, and public participation. Municipalities must develop infrastructure and public services. Subdistrict administrative organizations play a role in improving quality of life and the environment. Provincial administrative organizations are key mechanisms for provincial-level development, including education, public health, and tourism. The components of modern administration include developmental organizational leadership, strategic planning aligned with local potential, stakeholder participation, internal knowledge management, continuous human resource development, transparent management, and participatory monitoring and evaluation. Appropriate modern organizational management models include universal access to information, high-performance organizations, learning organizations, customer focus, flexible structures, enabling personnel participation, and organizational excellence through innovation and continuous quality management.